EXPLORING LINGUISTIC POLARITY DISPLAYED IN ALICEâ€™S â€œADVENTURES IN WONDERLANDâ€: A SYSTEMIC FUNCTIONAL LINGUISTIC PERSPECTIVE - Sholihah, Husna Imro'athush (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2020)
Short story is an interesting texts for promoting linguistic awareness and language acquisition, e.g. English young learners. It is important to introduce them with the linguistics features, e.g. subject-finite in their early ages of language learning especially in second and foreign languages. In respecting to the students character building, short stories are enriched of doctrines and philosophy which are fruitful for their psychological development, e.g. characters. Therefore, this study aims to analyze finites of linguistic polarity found in Alice?s Adventure in Wonderland. This is interesting as it leads to linguistics awareness. Adopting Bustam & Rayhan?s (2012) transitivity analysis model of Systemic Functional Linguistics (SFL) Approach, this exploratory research identified linguistic polarity of the attitudes of the story. The findings show that finite processes realize the polarity of attitudes utterances. Behavioral mental process are realized through finite to sharpen the attitudes in the story.